Contrast-enhanced harmonic endoscopic ultrasonography for differential diagnosis of pancreatic cysts - Kamata, Ken; Kitano, Masayuki; Omoto, Shunsuke; Kadosaka, Kumpei; Miyata, Takeshi; Yamao, Kentaro; Imai, Hajime; Sakamoto, Hiroki; Harwani, Yogesh; Chikugo, Takaaki; Chiba, Yasutaka; Matsumoto, Ippei; Takeyama, Yoshifumi; Kudo, Masatoshi (Endoscopy, 2016)
Background and study aim: Comparison of fundamental B-mode endoscopic ultrasonography (FB-EUS) and contrast-enhanced harmonic endoscopic ultrasonography (CH-EUS) in the differential diagnosis of pancreatic cysts according to presence of mural nodules. Patients and methods: Between April 2007 and April 2012, FB-EUS and CH-EUS data were prospectively collected from 581 consecutive patients with pancreatic cysts, and were retrospectively analyzed from 70 with subsequent cyst resection. Presence and height of mural nodules as detected on FB-EUS and CH-EUS were evaluated, and thence accuracies of both methods for diagnosing mucinous versus nonmucinous and malignant versus benign cysts.Results: On pathological examination 48 cysts were mucinous and 22 were nonmucinous; 30 cysts were malignant (high grade dysplasia or invasive carcinoma) and 40 were benign. If presence of a mural nodule was considered to indicate a mucinous cyst, FB-EUS and CH-EUS accuracies did not differ significantly (respectively: sensitivity 85 % vs. 79 %; specificity 46 % vs. 96 %; accuracy 73 % vs. 84 %, P = 0.057). If presence of mural nodule was considered to indicate malignancy, CH-EUS was significantly more accurate than FB-EUS (respectively: sensitivity 97 % vs. 97 %; specificity 75 % vs. 40 %; accuracy 84 % vs. 64 %, P = 0.0001). For diagnosing malignancy by evaluating mural nodule height, the area under the receiver operating characteristic (AUROC) was 0.84 and 0.93 for FB-EUS and CH-EUS, respectively (P = 0.028). Presence of a mural nodule of height ≥ 4 mm on CH-EUS was a sign of malignancy (false-positive fraction 0.2; true-positive fraction 0.93; odds ratio 56.0). Conclusions: CH-EUS is more accurate than FB-EUS for diagnosing malignant pancreatic cysts.